إدارة الأزمات في المشافي الحكومية في مدينة اللاذقية - اصبيرة, ولاء; داؤد, نسرين; طعمان, براءة (Latakia University Journal -Medical Sciences Series, 2018)
Hospitals are among the most vulnerable to crises and disasters. An effective management system is essential to deal with these crises. Therefore, this descriptive study aims to assess the availability of a crisis management system from the point of view of 718 workers in the governmental hospitals in Lattakia (Al Assad, Tishreen and National) which were selected in a random conveniently method, using a tool developed by the researcher for this purpose. The study findings were the availability of the five elements of crisis management in the three hospitals, but the stage of detection of early warning signals were not applied in Al Assad hospital, and there were significant variance between the hospitals of the study in crisis management. The study recommended strengthening interaction between management and staff, conducting periodic education and training sessions, applying virtual experiences to deal with potential crises, and developing renewed crisis forecasting mechanisms. تعتبر المستشفيات من أكثر المنظمات قابلية للتعرض للأزمات والكوارث، لذلك يشكل وجود نظام إداري فعَّال أمر ضروري للتعامل مع تلك الأزمات. بناءً على ذلك هدفت هذه الدراسة الوصفية إلى تقييم مدى توافر نظام إدارة الأزمات من وجهة نظر718 عامل في المشافي الحكومية في مدينة اللاذقية (مشفى الأسد الجامعي, والمشفى الوطني, ومشفى تشرين الجامعي) تم اختيارهم بطريقة العينة العشوائية المتاحة, باستخدام استبيان مطور من قبل الباحثة. وكان من أبرز النتائج في الدراسة توافر العناصر الخمسة لإدارة الأزمة في المشافي الثلاثة, لكن مرحلة اكتشاف إشارات الإنذار المبكر لم تكن متوافرة في مشفى الأسد, كما وجد تباين ذو دلالة إحصائية هامة بين مشافي الدراسة في إدارة الأزمات. و من أبرز التوصيات لهذه الدراسة تعزيز التفاعل بين الإدارة والعاملين, وإجراء دورات تثقيفية وتدريبية بشكل دوري وتطبيق تجارب افتراضية للتعامل مع الأزمات المحتملة, ووضع آليات متجدده للتنبؤ بالأزمات.